SINTESIS DAN KARAKTERISASI SILIKA GEL DARI ABU SEKAM PADI DENGAN MENGGUNAKAN NATRIUM HIDROKSIDA (NaOH) - Noor Hindryawati; Alimuddin Alimuddin (JURNAL KIMIA MULAWARMAN, 2010)
The synthesis and characterization of silica gel from rice hull ash by using NaOH has been done. The synthesis of silica gel from rice hull ash was done by incineration through a heating for 4 hours with the temperature variation at 700oC, 800 oC, and 900 oC. The product (Rice hull ash) washed with H2SO4 and then continued with Na2EDTA. The silica gel can be synthesized from the rice hull ash by adding H2SO4 solution into the Sodium Silicate (Na2SO3) at temperature 500oC for 30 minutes. The silica gel from the synthesis can be characterized using infrared spectroscopy and X-Ray diffraction. The result of this research showed the same pattern with the comparator silica gel (Kiesel gel 60).